PENGGUNAAN APLIKASI QUIZIZZ DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA MANDARIN SISWA KELAS 2 SMP KEMALA BHAYANGKARI - Annisa, Camelia Inas; Veronica, Tjen; Khiong, Bun Yan (Universitas Tanjungpura, 2023)
Quizizz is a application that contains online quiz games, which are mainly designed for students to play and learn at the same time. The purpose of the author's study using Quizizz application is to find out whether the use of Quizizz application is effective in improving the vocabulary mastery of Mandarin language among the second grade students of Kemala Bhayangkari Junior High School. In addition, to analyze the students' response to the use of Quizizz application. The author conducted the study using experimental, test and questionnaire methods in the second grade of Kemala Bhayangkari Junior High School. According to the results of this study, it can be seen that the students' post-test scores are higher than the pre-test scores; the average score of the students on the pre-test is 56.4, while the average score of the students on the post-test has increased to 84.5 after using the Quizizz application. Therefore, the use of Quizizz application is effective in improving Mandarin vocabulary mastery. The students' responses to Quizizz were summarized as follows: practicing vocabulary with Quizizz was fun and satisfying for the students, and they had no problems using all the features of Quizizz.